Avant-garde fascism the mobilization of myth, art, and culture in France, 1909-1939 - Antliff, Mark 1957- (Duke University Press, 2007)
Fascism, modernism and modernity -- The Jew as anti-artist : Georges Sorel and the aesthetics of the anti- Enlightenment -- La Cité française : Georges Valois, Le Corbusier and fascist theories of urbanism -- Machine primitives : Philippe Lamour and the fascist cult of youth -- Classical violence : Thierry Maulnier and the legacy of the Cercle Proudhon
Includes bibliographical references and index
Keywords: Sorel, Georges / 1847-1922; Avant-garde (Aesthetics) / History / 20th century / France; Fascism and art / History / 20th century / France; Fascism and culture / History / 20th century / France; Fascism / History / 20th century / France